2012
DOI: 10.1071/en11163
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterisation of humic-like substances from urban, rural and tropical biomass burning environments using liquid chromatography with UV/vis photodiode array detection and electrospray ionisation mass spectrometry

Abstract: Environmental context. One of the most important classes of water-soluble organic compounds in continental fine and tropical biomass burning aerosol is humic-like substances (HULIS), which contain components with strong polar, acidic and chromophoric properties. We focus on the chemical characterisation of HULIS and provide evidence that nitro-aromatic catecholic compounds are among the major species of HULIS. This indicates that volatile aromatic hydrocarbons emitted during biomass burning are important gas-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
153
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(162 citation statements)
references
References 53 publications
(121 reference statements)
9
153
0
Order By: Relevance
“…However, it is found that the HULIS samples isolated from different environments or sources, and from aerosol samples collected in different seasons can have different properties (Salma et al, , 2010Wex et al, 2007;Lin et al, 2010;Claeys et al, 2012;Fan et al, 2012;Song et al, 2012). Therefore, further efforts will be required in the future to comparative study the HULIS isolating methods, possibly using different HULIS samples isolated from rural, marine and biomass burning aerosol samples, and aerosol samples in different seasons.…”
Section: Environmental Significancementioning
confidence: 99%
“…However, it is found that the HULIS samples isolated from different environments or sources, and from aerosol samples collected in different seasons can have different properties (Salma et al, , 2010Wex et al, 2007;Lin et al, 2010;Claeys et al, 2012;Fan et al, 2012;Song et al, 2012). Therefore, further efforts will be required in the future to comparative study the HULIS isolating methods, possibly using different HULIS samples isolated from rural, marine and biomass burning aerosol samples, and aerosol samples in different seasons.…”
Section: Environmental Significancementioning
confidence: 99%
“…This approach has been recently used in the study of nitrogen-containing compounds with chromophoric properties such as nitroaromatics and imidazoles. 333,44 But the level of identification in complex mixtures remains low and coupling high resolution MS with HPLC/UV-Vis detection is necessary to increase it.…”
Section: D) Lc-uv and Lc/nmrmentioning
confidence: 99%
“…Some atmospheric aerosols have been found to contain light-absorbing macromolecular fractions having properties similar to those of humic substances, and therefore termed humic-like substances. 333,354,491,498 However, the definition of atmospheric HULIS being based on their extraction procedure, 491,498a,498b it is difficult to attribute them to a single compound or source. HULIS are often linked to biomass burning aerosols 491 but have also been found in a wide range of atmospheric aerosols, including rural and remote ones.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sources of SOA are biogenic VOCs such as terpenes (Fry et al, 2014). HULISs contain polyphenolic redox mediators such as catechol and nitro-catechols (Claeys et al, 2012;Hoffer et al, 2004;Ofner et al, 2011;Pillar et al, 2014).…”
Section: Oxidation Of Organic Aerosol Particles Containing Black and mentioning
confidence: 99%